ICT and curriculum change - Voogt, Joke; Pelgrum, Hans (Human Technology, 2005)
The change towards the information society implies that many countries have to change their curricula, because students need to develop competencies that are not addressed in the traditional curricula. A case study approach was applied to examine curriculum changes in ICT-supported pedagogical practices from 28 countries. The analysis focused on curriculum content and goals of the ICT-supported pedagogical practices, how these aims were implemented in practice and which outcomes for students and teachers could be observed. The results showed that the curriculum content often was not new but rather was delivered in a different way. Many ICT-supported pedagogical practices strove to realize new goals important for lifelong learning in an information society. Content and goals were offered in curricular settings, often crossing the traditional boundaries of academic subjects. In many of the cases students worked on topics that were meaningful to them.